Malignant mesenchyma - Falconi, Luis M (Cirugía del Uruguay, 1973)
Malignant mesenchymoma is a low-frequency tumor oi soft parts, generally localized in the muscle, with tenacious local and regional recurrency causing metastasis in 50 % of cases, through the bloodstream. It is predominant in females. Histogenesis is complex and it is admited that they result in multipotential differenciation capacity of primitive mesenchymatic cell in different tissues.